Do practical laboratory indices predict the outcomes of children with Henoch-Schönlein purpura?. Issue 4 (19th May 2019) - Ekinci, Rabia Miray Kisla; Balci, Sibel; Sari Gokay, Sinem; Yilmaz, Hayri Levent; Dogruel, Dilek; Altintas, Derya Ufuk; Yilmaz, Mustafa
ABSTRACT: Objectives : Henoch Schönlein Purpura (HSP) is the most common systemic vasculitis of childhood and often has a self-limiting course. We aimed to study whether practical laboratory parameters at the diagnosis predict disease course including recurrence and nephritis in addition to severe gastrointestinal involvement in children with HSP. Methods : This retrospective cohort study included 214 HSP patients, 43.5% (n = 93) female and 56.5% (n =121) male, who were diagnosed in our department. Laboratory parameters before treatment, including neutrophil, lymphocyte and platelet counts, mean platelet volume (MPV), neutrophil-to-lymphocyte (NLR), and platelet-to-lymphocyte ratios (PLR) were obtained retrospectively. Age at diagnosis, duration of follow-up, gender, preceding infections, medications, arthritis and arthralgia, abdominal pain, severe GI involvement, invagination, renal involvement and presence of nephritis, outcomes, and presence of recurrences were retrospectively recorded from medical files. Severe GI involvement was determined as severe colicky abdominal pain, bowel edema in ultrasonography or overt GI bleeding. A relapse was defined as a new flare of cutaneous lesions or other manifestations in a patient at least four asymptomatic weeks after the initial HSP episode. Results : Mean age at diagnosis was 7.6 ± 3.1 years. Biopsy-proven nephritis was found in 16 (7.5%) patients. Severe GI involvement was present in 77 (36%) patients, whereas only 12 (5.6%) patients were diagnosed with intussusception and in 29 (13.5%) patients, HSP recurred. Neutrophil count and NLR were found higher in HSP patients with severe gastrointestinal involvement and biopsy-proven nephritis. Additionally, only platelet count was lower and MPV was higher in patients with recurrent HSP. Conclusion : Elevated neutrophil count and NLR may be relevant markers for severe GI involvement and nephritis, whereas platelet count and MPV were the only laboratory parameters associated with disease recurrence.